Electrochemical Machining Properties of the Laser Rapid Formed Inconel 718 Alloy in NaNO3 Solution. Issue 14 (1st January 2017) - Wang, Xindi; Qu, Ningsong; Guo, Pengfei; Fang, Xiaolong; Lin, Xin
Abstract : Laser rapid forming (LRF) is a newly developed method of additive manufacturing that has drawn much attention owing to its outstanding advantages. However, direct formation of components with high precision and high surface quality through LRF is extremely time-consuming and expensive. To address this problem, electrochemical machining (ECM) was introduced as a subsequent finishing process. In this paper, electrochemical machining property of the laser rapid formed (LRFed) Inconel 718 alloy (both as-deposited and solution-annealed) was studied. On as-deposited LRFed sample, polarization behavior and current efficiency show isotropy, despite the anisotropy of the microstructure. After a solution annealing treatment, the polarization behavior shows no difference, but the material will be more difficult to machine. The surface topography after ECM shows anisotropy on as-deposited LRFed sample, and dendrites as a microscopic structure and layer-band (on vertical sections) as a macroscopic structure are noticeable. The height of layer bands and surface roughness (Ra) decrease with increasing current density. On solution-annealed sample, the dissolved surface was smooth and no subgrain boundaries or layer bands were observed. Finally, deep-small hole, grooves and flat surfaces were produced successfully through ECM.